2021
DOI: 10.3390/ijerph18052359
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity as a Mediator of the Relationship between Discrimination and Psychological Well-Being in South—South Migrant Populations

Abstract: There is abundant evidence about the negative impact of discrimination on well-being, but less research on factors that can reduce this negative effect, mainly focused on North American samples and with incipient development on South–South migration. The objective of this research was to analyze the effect of ethnic identity on the relationship between the experience of racial and ethnic discrimination and psychological well-being in Colombian immigrants living in Chile. A total of 962 immigrants over the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
(67 reference statements)
1
10
0
1
Order By: Relevance
“…In the present research, the scale for ethnic discrimination had an Alpha of 0.91, while the scale for racial discrimination had an Alpha of 0.93. We have assessed ethnic discrimination separately from racial discrimination, as there is evidence from previous studies that the two types of discrimination function differently [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, the scale for ethnic discrimination had an Alpha of 0.91, while the scale for racial discrimination had an Alpha of 0.93. We have assessed ethnic discrimination separately from racial discrimination, as there is evidence from previous studies that the two types of discrimination function differently [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In migrant populations, two of the most studied types of discrimination are those based on ethnicity and race, which have been associated with poorer physical and mental health [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], low self-esteem [ 25 , 26 ], and reduced well-being [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the aim of the present research is to evaluate the mediating effect that both ethnic identity and collective self-esteem may have on the inverse relationship between the presence of symptoms associated with mental health problems and QoL. We believe that there could be a mediating effect of ethnic identity and collective self-esteem since it has been found that these variables have been able to absorb the negative effect that various variables may have on indicators of well-being in other studies in a similar population [ 23 , 26 , 28 ], possibly exercising a protective role through the strengthening of individual self-esteem, which could be extrapolated to the case of quality of life.…”
Section: Introductionmentioning
confidence: 96%
“…This research focuses on south-south migration, i.e., people moving from one South American country to another, and in this particular case, Colombians to Chile. Our research group has provided evidence of the influence of negative factors such as discrimination on both their QoL and mental health, as well as reporting the protective effect that ethnic identity and collective self-esteem seem to have on the negative effects that discrimination has on well-being, QoL, or mental health [ 23 , 24 , 25 , 26 , 27 ]. In this context, the aim of the present research is to evaluate the mediating effect that both ethnic identity and collective self-esteem may have on the inverse relationship between the presence of symptoms associated with mental health problems and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic identity has been operationalized as a construct that contains two essential dimensions: exploration, which refers to efforts to learn more about one's own ethnic group about its cultural practices by participating in them, and, on the other hand, commitment, which refers to the degree of involvement and sense of belonging that the individual maintains with his or her ethnic group, which is characterized by a high degree of personal investment in the group. Several works have presented ethnic identity as a variable that positively affects the psychological well-being of migrants (Phinney et al, 2001;Smith and Silva, 2011;Balidemaj and Small, 2019), being a protective factor against the negative effects of perceived discrimination (Brittian et al, 2015;Cobb et al, 2019;Urzúa et al, 2021) or acculturation stress (Hun et al, 2021a,b).…”
Section: Introductionmentioning
confidence: 99%